The impact of obesity on walking and cycling performance and response to pulmonary rehabilitation in COPD - Bourbeau Jean; Breton Marie-Josée; Bernard Sarah; Laviolette Louis; Sava Francesco; Maltais François (BMC Pulmonary Medicine, 2010)
Abstract Background We examined the influence of overweight and obesity on pulmonary function, exercise tolerance, quality of life and response to pulmonary rehabilitation in COPD. Methods 261 patients with COPD were divided into three groups: normal body mass index (BMI), overweight and obese. Baseline and post rehabilitation pulmonary function, 6-min walking test (6MWT), endurance time during a constant workrate exercise test (CET) and St. George's Respiratory Questionnaire (SGRQ) scores were compared between all three classes of BMI. Results At baseline, obese and overweight patients had less severe airflow obstruction compared to normal BMI patients. There was no baseline difference in CET performance or SGRQ scores across BMI classes and 6MWT was reduced in the presence of obesity (p < 0.01). Compared to baseline, post-rehabilitation 6MWT, CET performance and SGRQ scores improved significantly in each group (p < 0.01), but 6MWT was still significantly lower in the presence of obesity. Conclusions Walking, but not cycling performance was worse in obese patients. This difference was maintained post rehabilitation despite significant improvements. Weight excess may counterbalance the effect of a better preserved respiratory function in the performance of daily activities such as walking. However, obesity and overweight did not influence the magnitude of improvement after pulmonary rehabilitation.